Diffusion-Weighted Magnetic Resonance Imaging in Patients with Prostate Cancer Treated with Radiotherapy. Issue 1 (January 2016) - Iannelli, Giancarlo; Caivano, Rocchina; Rago, Luciana; Simeon, Vittorio; Lotumolo, Antonella; Rabasco, Paola; Villonio, Antonio; Gioioso, Matilde; Mastrangelo, Pietro; Barchetti, Flavio; Panebianco, Valeria; Macarini, Luca; et al.
Aims: To evaluate the utility of a multiparametric 3T magnetic resonance imaging (MRI) study using diffusion-weighted images (DWI) for the assessment of prostate cancer before and after radiotherapy (RT). Methods: A total of 34 patients, who received a histologic diagnosis of prostate adenocarcinoma, underwent MRI examination before and after local RT for the assessment of response to treatment. Apparent diffusion coefficient (ADC) values were calculated and compared. Results: Before RT, DWI shows pathologic restriction of signal, while after RT pathologic restriction of signal was reduced or disappeared. The ADC values were significantly increased after therapy (p<0.05). Conclusions: The use of DWI with ADC measurements may be an imaging biomarker in the assessment of prostate cancer.